Estrategias metodológicas y su incidencia en el logro de destrezas con criterios de desempeño del bloque curricular de estadística y probabilidades en los estudiantes del octavo año de educación general básica de la unidad educativa Calasanz de la ciudad de Loja, período 2012-2013 - Pogo Agila, Iliana Elizabeth (2014)
The present investigation refers to the methodological strategies and its incidence on the skills achieved with performance criterions Curricular Block of Statistic and Probabilities in eighth year students of the Education General Basic the Calasanz Educative Unit of the city of Loja, period 2012-2013. The specific objectives that guide the present investigative work are:  To analyze the criterions that he takes into account the educational one for the selection and design of the methods and technical that applies in the boarding of the Curricular Block of Statistic and Probabilities.  To describe the characteristics that have the dexterities with acting approaches that the students develop in the Curricular Block of Statistic and Probabilities.  To formulate recommendations that allow to innovate the methodological strategies and to develop the dexterities with approaches of acting that contemplates the Upgrade and Curricular Invigoration of the Education Basic General for the Curricular Block of Statistic and Probabilities. The methodology used was based on inductive and deductive methods, applying the survey technique for the collection of the information of the field. The results obtained in the present investigation, are synthesized in the following terms:  According to the obtained in the field investigation is concluded that the methodological strategies used in the teaching-learning Curriculum Block Statistics and Probabilities in eighth year students of the Education General Basic the Calasanz Educative Unit of the city of Loja, process are inefficient for the skills achieved with performance criterions.  Also do not is evidence from of teaching a variety methods and implementing appropriate for application in the development of content Curricular Block of Statistic and Probabilities so there is not the attainment of the skills achieved with performance criterions in eighth year students of the Education General Basic. With these records he thinks about as alternative limits: Development of the Curricular Block of Statistic and Probabilities, using appropriate methodological strategies to facilitate students of eighth year students of the Education General Basic the skills achieved with performance criterions.